Metabolic rewiring promotes anti-inflammatory effects of glucocorticoids - Auger, Jean-Philippe; Zimmermann, Max; Faas, Maria; Stifel, Ulrich; Chambers, David; Krishnacoumar, Brenda; Taudte, R. Verena; Grund, Charlotte; Erdmann, Gitta; Scholtysek, Carina; Uderhardt, Stefan; Ben Brahim, Oumaima; et al. (Nature, 2024)
Glucocorticoids represent the mainstay of therapy for a broad spectrum of immune-mediated inflammatory diseases. However, the molecular mechanisms underlying their anti-inflammatory mode of action have remained incompletely understood1. Here we show that the anti-inflammatory properties of glucocorticoids involve reprogramming of the mitochondrial metabolism of macrophages, resulting in increased and sustained production of the anti-inflammatory metabolite itaconate and consequent inhibition of the inflammatory response. The glucocorticoid receptor interacts with parts of the pyruvate dehydrogenase complex whereby glucocorticoids provoke an increase in activity and enable an accelerated and paradoxical flux of the tricarboxylic acid (TCA) cycle in otherwise pro-inflammatory macrophages. This glucocorticoid-mediated rewiring of mitochondrial metabolism potentiates TCA-cycle-dependent production of itaconate throughout the inflammatory response, thereby interfering with the production of pro-inflammatory cytokines. By contrast, artificial blocking of the TCA cycle or genetic deficiency in aconitate decarboxylase 1, the rate-limiting enzyme of itaconate synthesis, interferes with the anti-inflammatory effects of glucocorticoids and, accordingly, abrogates their beneficial effects during a diverse range of preclinical models of immune-mediated inflammatory diseases. Our findings provide important insights into the anti-inflammatory properties of glucocorticoids and have substantial implications for the design of new classes of anti-inflammatory drugs.
CRIS-Team Scopus Importer:2024-04-19

Protektive Makrophagen: Neue Einblicke zur Rolle von Synovialmakrophagen bei entzündlichen Gelenkerkrankungen - Knab, Katharina; Chambers, David; Krönke, Gerhard (Zeitschrift für Rheumatologie, 2021)
Macrophages are among the phylogenetically oldest cells of the immune system and are found in all tissues and organs. In addition to playing an important role in immune response against pathogenic microorganisms, these cells were previously described to play a vital role in chronic inflammatory diseases such as rheumatoid arthritis. Using novel techniques such as single-cell sequencing and advanced microscopy techniques it has now been shown that macrophages are far more versatile. Thus, these cells contribute considerably to tissue homeostasis and tissue regeneration. As each tissue has to fulfill special requirements, macrophages vary in their phenotype and function between organs. New data have now identified a specialised population of epithelioid macrophages that exert a protective and anti-inflammatory function in synovial tissue and prevent the initial onset as well as episodes of joint inflammation in rheumatoid arthritis.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Macrophage heterogeneity; Macrophage ontogeny; Resident macrophages; Synovial macrophages; Synovial microenvironment

Selective CAR T cell–mediated B cell depletion suppresses IFN signature in SLE - Wilhelm, Artur; Chambers, David; Müller, Fabian; Bozec, Aline; Grieshaber Bouyer, Ricardo; Winkler, Thomas; Mougiakakos, Dimitrios; Mackensen, Andreas; Schett, Georg; Krönke, Gerhard (JCI Insight, 2024)
Applying advanced molecular profiling together with highly specific targeted therapies offers the possibility to better dissect the mechanisms underlying immune-mediated inflammatory diseases such as systemic lupus erythematosus (SLE) in humans. Here we apply a combination of single-cell RNA-Seq and T/B cell repertoire analysis to perform an in-depth characterization of molecular changes in the immune-signature upon CD19 CAR T cell–mediated depletion of B cells in patients with SLE. The resulting data sets not only confirm a selective CAR T cell–mediated reset of the B cell response but simultaneously reveal consequent changes in the transcriptional signature of monocyte and T cell subsets that respond with a profound reduction in type I IFN signaling. Our current data, thus, provide evidence for a causal relationship between the B cell response and the increased IFN signature observed in SLE and additionally demonstrate the usefulness of combining targeted therapies and analytic approaches to decipher molecular mechanisms of immune-mediated inflammatory diseases in humans.
CRIS-Team Scopus Importer:2024-07-12

Synovial Macrophage and Fibroblast Heterogeneity in Joint Homeostasis and Inflammation - Knab, Katharina; Chambers, David; Krönke, Gerhard (Frontiers in Medicine, 2022)
The synovial tissue is an immunologically challenging environment where, under homeostatic conditions, highly specialized subsets of immune-regulatory macrophages and fibroblasts constantly prevent synovial inflammation in response to cartilage- and synovial fluid-derived danger signals that accumulate in response to mechanical stress. During inflammatory joint diseases, this immune-regulatory environment becomes perturbed and activated synovial fibroblasts and infiltrating immune cells start to contribute to synovial inflammation and joint destruction. This review summarizes our current understanding of the phenotypic and molecular characteristics of resident synovial macrophages and fibroblasts and highlights their crosstalk during joint homeostasis and joint inflammation, which is increasingly appreciated as vital to understand the molecular basis of prevalent inflammatory joint diseases such as rheumatoid arthritis.
CRIS-Team Scopus Importer:2022-09-09
Keywords: fibroblasts; inflammation; macrophages; rheumatoid arthritis; single-cell sequencing; synovial tissue